Influence of Sex and Physiological Traits on Kacang Goat Meat Tenderness - Al Gifari, Zaid; Firhamsah, Ikhwan; Anwar, Khairil; Ali, Muhamad; Firmansah, Firmansah (Jurnal Biologi Tropis, 2025)
Differences in meat tenderness between male and female animals are influenced by physiological and hormonal factors that affect muscle composition and connective tissue development. Understanding the effect of sex on meat tenderness is important for improving the quality of local goat breeds such as the Kacang goat, which is commonly raised under traditional semi-intensive systems. This study analyzed and compared the tenderness profile of meat from one-year-old male and female Kacang goats reared semi-intensively. Meat samples from the loin and shank of three male and three female goats were collected and tested using the Warner–Bratzler Shear Force (WBSF) method, and data were analyzed using an independent t-test to determine differences in tenderness between muscle types and sexes. The results showed a significant difference in male goats, with shank meat being tougher than loin meat, while in female goats, tenderness between both cuts was relatively uniform. These variations are attributed to physiological and hormonal differences, particularly higher testosterone levels in males that increase connective tissue density in more active muscles. In conclusion, sex significantly influences the tenderness of Kacang goat meat, with females producing meat of more consistent tenderness across different cuts, whereas males exhibit greater variation. The findings contribute to a better understanding of sex-related factors affecting meat quality and provide a scientific basis for improving goat meat production and management practices.